Skills for the 21st century: Findings and policy lessons from the OECD survey of adult skills - John P. Martin (Institute of Labor Economics (IZA), 2018)
The OECD Survey of Adult Skills is the jewel in the crown of its Programme for the International Assessment of Adult Competencies (PIAAC). This paper argues that the findings and policy lessons from the project to date justify the high hopes which were placed in PIAAC when detailed planning for the project began in 2003. First, it presents a brief recap of PIAAC and its two predecessor international skills surveys. Second, it outlines the main themes which have been investigated to date using data from PIAAC. Third, the main findings and policy lessons drawn from PIAAC are highlighted. Finally, looking forward to the second cycle of PIAAC, for which planning is now underway, the paper suggests some priority areas for improvements to the survey design in order to add to its analytical usefulness and enhance its utility to policy makers.
Keywords: I24; I26; J24; J62; M53; 330; PIAAC; skills; returns to skills; skills mismatch; skills use; lifelong learning